An unusual case of carotid dissection. Issue 6 (18th June 2010) - Mazhary, S; Dev, S; Mentzer, A
Abstract : Carotid dissection is a rare, but potentially fatal, cause of ischaemic stroke in young patients. It occurs when a small tear forms in the tunica intima of the arterial wall creating a space between the inner and outer layers of the vessel where blood can enter and form a haematoma. This can cause a stenosis or complete occlusion. Thromboembolic events are thought to be the cause of infarction in the majority of cases of stroke, rather than haemodynamic insufficiency, in patients with carotid dissection. Although traditionally thought to be most commonly caused by head or neck trauma, spontaneous carotid dissection is now an increasingly recognised cause of stroke in young patients. Clinical signs can often be subtle, with mild cerebral or cranial nerve dysfunction. Here, a case is reported of a spontaneous internal carotid artery dissection in a previously well 38-year-old man. An appropriate imaging modality is important to confirm the diagnosis before commencing anticoagulation treatment.